Comparação da dinâmica populacional e identificação dos estoques pesqueiros do camarão sete-barbas Xiphopenaeus kroyeri (Heller, 1862) (Decapoda, Penaeidae) no litoral brasileiro - Davanso, Thiago Maia [UNESP] (2015)
Considering that fishing industry is responsible for almost 40% of world food supply, studies involving species commercially exploited in main Brazilian states are of great importance for the sustainable use of this resource. The present study investigated the population dynamics (population structure, growth and longevity, correlation between reproductive females and juveniles with environmental factors, sexual maturity, reproductive periods and recruitment and sex ratio) of the seabob shrimp Xiphopenaeus kroyeri, comparing two regions of southeastern Brazil. One region is located above but adjacent to the Cabo Frio upwelling (Macaé-RJ; 22º 37'S and 41º 78'W) on the coast of Rio de Janeiro state; the other region is located below and far from the mentioned upwelling (Ubatuba-SP, 23º27'S e 45º02'W), on the coast of São Paulo state. Additionally, population samples of the seabob shrimp collected in eight regions of Brazilian coast were compared using traditional morphometry analysis. A shrimp boat equipped with double-rig trawl nets was used for biological material sampling. Environmental factors were sampled with a Van Dorn bottle (surface and bottom water) and a Van Veen sediment collector. Temperature and salinity were measured from water samples, as well as chlorophyll-a was quantified. The mean sizes of the shrimp sampled in Macaé region were higher in all demographic categories (juveniles, adults and reproductive male and female) when compared to that sampled in Ubatuba region. Females were significantly higher and had greater longevities when compared to males in both regions. Both lower temperature values and greater longevities in Macaé region may have driven the variation in size when compared to Ubatuba sizes. In Macaé, reproductive females and juveniles correlated with organic matter content, and juveniles correlated with bottom water salinity. In Ubatuba, just chlorophyll-a had a correlation with reproductive ...